1999
DOI: 10.1161/01.atv.19.10.2568
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin G20210A Gene Mutation and Further Prothrombotic Risk Factors in Childhood Thrombophilia

Abstract: Abstract-Risk factors for venous thrombosis in adults are the prothrombin G20210A and the factor V (FV) G1691A mutations and hereditary deficiencies of protein C, protein S and antithrombin. However, data are limited on the relevance of these risk factors for thrombosis in children and adolescents. We therefore investigated 261 patients aged 0 to 18 (median 5.7 years, 48% male) with venous thrombosis and controls (nϭ370) for the presence of prothrombotic risk factors including the prothrombin G20210A mutation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 29 publications
8
95
2
5
Order By: Relevance
“…18,19 The prevalence of the MTHFR667 mutation in our study was 41% in the heterozygous state, and 10% in the homozygous state, again comparable to previously published studies. 20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…18,19 The prevalence of the MTHFR667 mutation in our study was 41% in the heterozygous state, and 10% in the homozygous state, again comparable to previously published studies. 20 The prevalence of MTHFR1298 mutation in our study was comparable to the wide range of incidence reported in the United States population. 33 Previous studies have reported an increased prevalence of FVL and MTHFR mutations in neonates and children with thrombosis compared to the general population 16,34 and have also shown an increased risk of catheter-related thrombosis in patients with FVL; 12,13 however, we found no difference in the prevalence of MTHFR mutations and FVL mutation in infants with and without thrombosis.…”
Section: Discussionsupporting
confidence: 85%
“…This genetic mutation is present in 1 to 2% of the general population but the prevalence is 4 to 20% in selected high-risk groups such as patients with thrombosis. 20 Methylene-tetrahydrofolate reductase (MTHFR) 677C>T (MTHFR667) and MTHFR1298A>C (MTHFR1298) mutations cause altered MTHFR activity leading to increased plasma levels of homocysteine, 16,[20][21][22] especially in folate-deficient patients. Hyperhomocystenemia has been associated with an increased risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of protein S deficiency was based on reduced free protein S antigen levels combined with decreased or normal total protein S antigen concentrations respectively. Criteria for the hereditary nature of a haemostatic defect were its presence in at least one further first-or second-degree family member and/or the identification of a causative gene mutation (Ehrenforth et al, 1999a;Junker et al, 1999;Nowak-Go Èttl et al, 1999). Fasting homocysteine concentrations within the first year of life were classified as increased when repeated measurements were found .…”
Section: Methodsmentioning
confidence: 99%
“…Platelet-poor plasma was prepared by centrifugation at 3000 ϫ g for 20 min at 4°C, aliquoted in polystyrene tubes, stored at Ϫ70°C, and thawed immediately before the assay procedure (16). Amidolytic protein C and antithrombin activities were measured on an ACL 300 analyzer (Instrumentation Laboratory, Munich, Germany) using chromogenic substrates (Chromogenix, Møln-dal, Sweden).…”
Section: Plasma-based Assaysmentioning
confidence: 99%